(untitled) - Sluiter, Liesbeth (Bangkok, 1992)
The book captures lives and times of a river in poignant texts and intimate photo's the life of South-East Asia's mightiest river. Millions of people in Laos, Thailand, Cambodia and Vietnam enjoy its wealth of fish, floodwaters and fertile mudplains. The river and its people are under direct threat. Prestigious dam projects are planned, which will alter the character of the river, affect the supply of water downstream, and force hundreds of thousands of people to resettle. The economic benefits of the dam projects are dubious. Controversy on the value of dams rages both in the North and the South, as the wealth generated by large dams usually flows to urban and industrial elites and influential landowners, at the expense of rural communities
Keywords: Water resources development,Mekong River Watershed; Mekong River watershed,Economic conditions